MENINGKATKAN KETRAMPILAN KOMUNIKASI TERTULIS MELALUI PENDEKATAN PERSPEKTIF - Budi Andayani; Amitya Kumara (Jurnal Psikologi, 1999)
Expressing ideas successfully requires a writer’s ability in imagining how his/her readers will interpret his/her writing. The present research is replicating a part of Traxler and Gernsbacher’s research (1993) comparing between experimental group with selection task and control group with rating task. The experiment uses tangram geometric pictures of Traxler and Gernsbacher’s research (1993) to be described by the writers. The activity proceeds in three meetings each with one-week interval, either for the writer or the reader groups. The subjects are students of the Faculty of Psychology GMU presently writing their undergraduate thesis. The overall thirty-two students were assigned into three groups. Eight students were assigned as experimental writers with the selection task and another eight students were as control writers with the rating task. The rest were readers whose task was to read two writings of two writers of different writing groups. The data was the sum of pictures identified correctly by the readers on the basis of the writers’ description. Data analysis shows that there is no obvious difference between the experiment and control group in the improvement of writing skill (a student-t test analysis upon the difference of the mean of readers’ improvement between session 1 and 3, between experiment and control group is t=0.816; p